ANALISIS AKUNTABILITAS, TRANSPARANSI DAN EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) (STUDI KASUS PADA SMP NEGERI 3 DAN SMP ISLAM YPUI DARUL ULUM DI KOTA BANDA ACEH) - Ammar, Faisyal; Bustamam, Bustamam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
The purpose of this study was to determine the implementation of accountability, transparency, and effectiveness in managing the School Operational Assistance (BOS) funds in public and private Junior High School in Banda Aceh City. This research involved two objects, Junior High School 3 Banda Aceh and Islamic Junior High School YPUI Darul Ulum. This research used the qualitative descriptive method and also used primary and secondary data in data collection. The primary data were obtained directly by interviewing informants that were BOS coordinator in Education and Culture Services of Banda Aceh City and school BOS team consisting of the school principal and BOS treasure. The data were collected by direct observation in the field. The secondary data were collected by using documentation technique. In analyzing the data, the researcher used data reduction, data presentation, and data verification. The result of the study showed that the accountability, transparency, and effectiveness in managing the School Operational Assistance (BOS) funds in Junior High School 3 Banda Aceh were in accordance with the Regulation of the Minister of Education and Culture (Permendikbud) No. 26 of 2017 which reflected good governance, while the management of the School Operational Assistance (BOS) funds in Islamic Junior High School YPUI Darul Ulum Banda Aceh in terms of transparency was still not perfect, but in terms of accountability and effectiveness were in accordance with the Regulation of the Minister of Education and Culture (Permendikbud) No. 26 of 2017.